The Role of Deposit Insurance in Microfinance Institutions: A Systematic Literature Review - Suhardiono; Hermanto Siregar (LP2M IAIN Palopo, 2026)
This study reviews how deposit insurance interacts with the operations, behavior, and stability of microfinance institutions (MFIs). Methods: A systematic literature review (SLR) was conducted using PRISMA-guided screening. Searches were run in five academic databases (Google Scholar, Web of Science, SpringerLink, Taylor & Francis Online, and ScienceDirect) using the string “deposit insurance” AND “microfinance,” producing 625 records. After removing duplicates and applying title/abstract and full-text screening, three studies met the final inclusion criteria and were synthesized. Results: The evidence shows three main patterns: (1) deposit guarantees can increase moral hazard in MFIs with weak governance (as seen in Indonesia’s rural banks), (2) depositor trust, often shaped by perceived safety, can reduce deposit volatility and panic withdrawals (as shown in Gabon), and (3) deposit insurance may shift higher-risk borrowers away from insured banks toward MFIs, changing where risk concentrates in the financial system. Implications: Deposit insurance policy should consider MFIs, not only commercial banks. If protection is extended to MFIs (fully or partly), it should be paired with stronger governance requirements, better supervision, and risk-based pricing to reduce moral hazard while supporting depositor confidence and financial inclusion